Phylogeny and divergence time estimation of the subfamily Amphipsyllinae based on the Frontopsylla diqingensis mitogenome - Pu, Ju; Lin, Xiaoxia; Dong, Wenge (Frontiers in Veterinary Science, 2024)
Fleas are primarily parasites of small mammals and serve as essential vectors of the transmission of plague. The subfamily Amphipsyllinae (Siphonaptera: Leptopsyllidae) consists of 182 species across 13 genera, widely distributed worldwide. Only two species of Amphipsyllinae have been sequenced for complete mitogenomes to date. It hinders the taxonomy and evolutionary history studies of fleas. In this study, we first sequenced the Frontopsylla diqingensis mitogenome and performed comparative mitogenomic analyses with the two other species (Frontopsylla spadix and Paradoxopsyllus custodis) in Amphipsyllinae available in the NCBI database. The evolutionary process of Amphipsyllinae was comprehensively analyzed in terms of nucleotide composition, codon usage, nucleotide diversity, tRNA secondary structure, nucleotide skew, phylogeny tree, and divergence time. Nucleotide diversity and tRNAs of three species of fleas of Amphipsyllinae have differences among different species. The effective number of codon (ENC)-plot, neutrality curve, PR2, and correspondence analysis (COA) showed that the codon preference of Amphipsyllinae was influenced mainly by natural selection. For phylogenetic trees and divergence time of the order Siphonaptera, our results showed two concatenated data matrices, namely, PCG: (((Ceratophyllidae + Leptopsyllidae) + ((Vermipsyllidae + Hystrichopsyllidae) + Ctenophthalmidae)) + (Pulicidae + Pygiopsyllidae)); PCGRNA: ((((Ceratophyllidae + Leptopsyllidae) + ((Vermipsyllidae + Hystrichopsyllidae) + Ctenophthalmidae)) + Pulicidae) + Pygiopsyllidae). We concluded that P. custodis and Macrostylophora euteles from GenBank are the same species by phylogenetic trees and sequence alignment, and supported the monophyly of Amphipsyllinae. Amphipsyllinae diverged in the Cenozoic, approximately 73.37–40.32 million years ago (Mya). The majority of the species within the intraordinal divergence into extant lineages occurred after the K-Pg boundary. The common ancestor of the extant order Siphonaptera diverged during the Cretaceous. Our findings supported those of Zhu et al. (1). This study provides new insights into the evolutionary history and taxonomy of the order Siphonaptera.